A Sociedade de Hiperconsumo e as marcas de Moda (ModaPalavra e-periódico, 2012)
The current society of hyperconsumption, as described by Gilles Lipovetsky, is characterized by the pursuit of happiness, what even justifies the consumption of objects. For this purpose, products and services for sale are impregnated with sensations and messages to stimulate feelings of happiness. That’s what brands do: pervade offers with soul, personality and sensory appeal. This paper describes the society of hyperconsumption and relates it to fashion brands which, by appreciating ephemerality and its time, stimulate consumption selling more than products: change, novelty and happiness. The research method employed in this work was the literature search, which covers the areas of philosophy – which deals with the consumer society –, fashion and brand management. The purpose of this paper is to perform a bibliographic consideration about the current (hyper)consumption society under the view of brands.
Keywords: Hyperconsumption; brands; fashion